1998
DOI: 10.1023/a:1008249214328
|View full text |Cite
|
Sign up to set email alerts
|

Detection of identical Hodgkin–Reed Sternberg cell specific immunoglobulin gene rearrangements in a patient with Hodgkin’s disease of mixed cellularity subtype at primary diagnosis and in relapse two and a half years later

Abstract: This finding indicates the existence of a clonal H-RS cell population during the first manifestation of HD and persistence and dissemination of this clone despite aggressive treatment. Thus, in the described case the malignant nature of H-RS cells defined by dissemination and recurrence of the identical H-RS cell clone in relapsing disease is proven.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Thus, PET obviously is able to detect emerging relapses some months before they can be displayed by CT scan, but, for technical reasons, the resolution of PET is presumably not good enough to detect minimal residual disease, which can cause late relapses (Ͼ 12 months) in HL. 15 Thus, a negative PET should predict PFS for at least 12 months in most cases.…”
Section: Response and Fdg-pet In Hodgkin Lymphoma 3991mentioning
confidence: 99%
“…Thus, PET obviously is able to detect emerging relapses some months before they can be displayed by CT scan, but, for technical reasons, the resolution of PET is presumably not good enough to detect minimal residual disease, which can cause late relapses (Ͼ 12 months) in HL. 15 Thus, a negative PET should predict PFS for at least 12 months in most cases.…”
Section: Response and Fdg-pet In Hodgkin Lymphoma 3991mentioning
confidence: 99%
“…Instead, they survive, clonally expand, and lead to disseminated tumor growth and clonal relapse. 25,26 Several studies have shown CD95/Fas expression by HRS cells. 27,28 However, cultured HRS cells are resistant to Fas-mediated apoptosis.…”
mentioning
confidence: 99%
“…The bone marrow cells (BMC) of the same patient whose peripheral blood cells were used to establish the cell line L1236, were harvested for autologous bone marrow transplantation during complete clinical remission (for case report of the patient see Jox et al (1998) and used as normal tissue control for determination of the patient's germ line allelotype.…”
Section: Bone Marrow Cellsmentioning
confidence: 99%
“…Therefore, the patient's bone marrow cells (BMC), which were obtained during complete clinical remission, were analysed to exclude minimal residual disease. The V H 1 gene rearrangement of L1236 cells was already used to detect the patient's H-RS cells in various tissues obtained during the course of the disease (Jox et al, 1998). To test the patient's BMC for the presence of H-RS cells a seminested PCR was performed.…”
Section: Analysis Of the Patient's Bone Marrow Cells For Minimal Resimentioning
confidence: 99%